Antivalstybinė Klaipėdos krašto nacionalsocialistų veikla ir priedangos organizacijos 1935-1937 metais - Valiukevičius, Mindaugas (Lietuvos istorijos studijos, 2006)
Nazi movement in Klaipėda region, alike any social-political phenomenon in the 1st half of the XX century, had its beginning and its end. The 1st national socialist organization in the region had been established as early as in 1928. In 10 years, i.e. in 1938 "nazification" of Klaipėda region was finished. Military tribunal decision to imprison SVG and CSA organizations’ leaders did not put an end to national-socialist movement. Around 1000 block and cell leaders remained free and carried on with their activities. Members of the forbidden SVG party and their supporters were restoring the national-socialist movement. A broad agent network had been established - informants and cooperatives had been recruited in „larger Lithuania" and its state institutions. With their help, nazis were successfully restoring their movement in Klaipėda region. Contacts with Germany were restored and constantly strengthened using the newly formed agent network. Undercover nazi movement in Klaipėda region had been attracting more and more local population. SVG leaders, probably instructed by Germany, divided the movement into 2 parts: 1) extremely carefully camouflaged, but absolutely legal activity in Klaipėda regional parliament, within the limits of its competence; 2) undercover - national-socialist propaganda distribution, "political education", military training and diversions. These features are the most typical for the period of 1935 to late 1937. National-socialist movement evolved into a new stage. The whole movement had been de-centralised - national-socialist information distribution sources had been established in almost all legally acting organizations in Klaipėda region. Religious, youth and sports organizations were the most politically engaged and propagandistic. All undercover activities of these organizations had been fine-tuned by a special A. Hitler’s directive for Klaipėda region issued in the end of November 1935. Though the period of 1935 to 1937 seems to be kind of blank (there were no large demonstrations with nazi war-cries and swastikas, there were no brutal terrorist acts, not even larger riots), but the anti-constitutional activity to strengthen the national-socialist movement was much more constructive.